Kinetic Aspects of the Interaction of Blood Clotting Enzymes - Hemker, H. C; Vermeer, C; Govers-Riemslag, J (Thrombosis and Haemostasis, 1977)
The relation between clotting time and the inverse of prothrombin concentration is shown to be rectilinear.